STUDI PERBANDINGAN PROSES PELINDIAN UNTUK EKSTRAKSI SKANDIUM DARI TERAK RESIDU BAUKSIT - Sariman; Rochani, Siti; Saleh, Nuryadi; Rodliyah, Isyatun; Dianawati, Erika Arum; Wijayanti, Retno (Balai Besar Pengujian Mineral dan Batubara tekMIRA, 2023)
Scandium is classified as a rare earth element. Its existences are geochemically in small amounts as associate minerals. Consequently, scandium production is minimally from processing residues of major minerals. Indonesia has large bauxite deposits, and it is processed into alumina, producing bauxite residue as a by-product. The bauxite residue contains rare earth metals, including scandium. In this study, various ways of extracting scandium from bauxite residue slag were carried out. The bauxite residue beneficiation process was done through a smelting reduction process followed by magnetic separation. Scandium extractions were carried out from the bauxite residue slag through a leaching process with concentrated sulfuric, sulfation, alkali fusion, and a 2-stage acid leaching. The best percentage of scandium extracted was obtained at 88.40%, using the 2-stage acid leaching at the acid concentration of 500 g/kg, the temperature of 90oC, and the leaching time at 3 hours for each leaching stage. In addition, the best neodymium extracted achieved 76,97%, using the alkali fusion, fused in NaOH at 700oC for 3 hours.